Clinical impact of intravascular ultrasound‐guided balloon angioplasty in patients with chronic limb threatening ischemia for isolated infrapopliteal lesion. Issue 3 (21st October 2020) - Soga, Yoshimitsu; Takahara, Mitsuyoshi; Ito, Nobuhiro; Katsuki, Tomonori; Imada, Kazuaki; Hiramori, Seiichi; Tomoi, Yusuke; Ando, Kenji
Abstract: Background: To estimate the impact of intravascular ultrasound (IVUS) in patients with chronic limb‐threatening ischemia (CLTI) who underwent balloon angioplasty for isolated infrapopliteal lesion. Methods: The study was performed as a single‐center, prospective maintained database, retrospective analysis. Between January 2013 and December 2018, consecutive 155 CLTI patients (155 limbs) who primarily underwent balloon angioplasty for de novo isolated infrapopliteal atherosclerotic lesions with Rutherford category class 4 or 5 were identified (IVUS‐guided: 92 patients, angio‐guided: 63 patients) and included in the analysis. We compared clinical outcomes in IVUS‐guided group with that in angio‐guided group. The primary endpoint was limb salvage without any reintervention. The main secondary endpoints were wound healing rate and time to wound healing in the tissue loss group. Result: Patient and limb characteristics were similar between the two groups. The IVUS‐guided group was treated with a larger balloon size for all types of below‐the‐knee vessel ( p  < .001), although lesion characteristics, including the QVA‐measured vessel diameter, were similar between the two groups. The IVUS‐guided group had a higher rate of limb salvage without any reintervention than the angio‐guided group ( p = 0028). Whereas limb salvage and overall survival was not significantly different. Wound healing was significantly earlier and the time to wound healing was significantly shorter (84 ± 55 days vs. 135 ± 118 days, p = .007) in the IVUS‐guided group. Conclusion: Limb salvage rate without any reintervention in IIVUS‐guided balloon angioplasty group was significantly higher than that in angio‐guided balloon angioplasty group in patients with CLTI due to isolated infrapopliteal disease.